The Effect of Ownership Structure On Dividend Policy in Mining Companies Listed On The Indonesia Stock Exchange in The Period 2021-2023 (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The purpose of this study is to ascertain how ownership structure affects dividend policy. The study's sample consisted of 22 mining businesses that were listed between 2021 and 2023 on the Indonesia Stock Exchange. Purposive sampling and panel data regression analysis were the sample strategies used in the investigation. The control variable was profitability, while the dependent variable was dividend policy. The independent variables were government, institutional, and foreign ownership. The findings demonstrate that dividend policy is negatively impacted by foreign ownership and profitability. Dividend policy is not significantly impacted by institutional ownership or the government. It is intended that by focusing on the amount of profit made such that shareholders receive dividend yield, this study would have ramifications for management of businesses. Prospective investors are also anticipated to use this study as a source of information to determine the amount of profit and dividend yield that the firm provides to its shareholders.